Spontaneous Chirality Induction in the Assembly of a Single Layer 2D Network with Switchable Pores. Issue 18 (27th March 2023) - Shen, Bowen; Pan, Chunyu; Feng, Xiaopeng; Kim, Jehan; Sun, Mo; Lee, Myongsoo
Abstract: Although two‐dimensional (2D) chiral sheet structures are attractive because of their unique chemical and physical properties, single layer 2D chiral network structures with switchable pore interior remain elusive. Here we report spontaneous chirality induction in a single layer 2D network structure formed from the self‐assembly of tetrapod azobenzene molecules. The chirality induction arises from multiple sublayers slipped in a preferred direction in which the sublayer consists of unidentical molecular arrangements in the in‐plane a and b directions, breaking both the plane of symmetry and inversion symmetry. The protruded azobenzene units in the pore interior can be selectively isomerized upon UV irradiation, resulting in a reversible deformation of the chiral pores while maintaining the 2D frameworks. The chiral network can thus selectively entrap one enantiomer from a racemic solution with near perfect enantioselectivity, and then release it upon UV irradiation. Abstract : Single layer chiral 2D network structures with photoswitchable internal cavities have been formed by the self‐assembly of azobenzene‐based tetrapod aromatic amphiphiles, with spontaneous chirality induction arising from the breaking of both the plane of symmetry and inversion symmetry. The chiral network structures can selectively catch one enantiomer from a racemic solution and then release it upon UV irradiation through reversible pore deformation.